Pengaruh Kombinasi Renolith Terhadap Stabilitas Tanah Pada Jalan Demuk Pucanglaban Tulungagung - Hermawan Hermawan; Agata Iwan Candra; Yosef Cahyo Setianto Poernomo (Kadiri University, 2020)
The soil structure consists of several mineral composition elements, namely clay, sand, and other minerals, such as rocks. Montmorillonite soil structures are soil structures that are mostly clays inside their components. The nature of montmorillonite-type soils is prone to deflection when loading when there is a change in the level of water dehydration. In the preparation of the following final project, the author tries to correlate the effect of the Renolith combination on soil stability. Clay material is from the location of Jalan Demuk,Pucanglaban Village, Tulungagung Regency. The combination of additives used as a correlation of soil stability is Renolith, with 0% (original soil), 5%, 10%, 15%,and 20%. The test method used is the method of soil classification, soil consistency limits, and soil compaction. The test results show that the original soil structure has montmorillonite activity value. In testing specimens with variations in the maximum combination (20%) of soil structure material and Renolith, The original soil Proctor testing 6.72 gr/cm3 and after combined with 20% Renolith increased to 10.56 gr/cm3.Struktur tanah terdiri dari beberapa unsur mineral penyusunannya, yaitu lempung, pasir dan mineral lain seperti batuan. struktur tanah bersifat monmorillonite adalah struktur tanah yang sebagian besar terdapat lempung didalam komponennya. Sifat dari tanah berjenis montmorillonite mudah mengalami lendutan ketika dilakukan pembebanan saat terjadi perubahan tingkat dehidrasi air. Pada penelitian ini diteliti korelasi pengaruh kombinasi renolith terhadap stabilitas tanah. Material tanah lempung diambil dari lokasi Jalan Demuk, Desa Pucanglaban, Kabupaten Tulungagung. Kombinasi bahan aditif yang digunakan sebagai korelasi stabilitas tanah adalah renolith dengan persentasejumlah 0%(tanah asli),5%,10%, 15%dan 20%.Metode pengujian yang digunakan adalah metode Â Â pemadatan tanah. Hasilpengujian benda uji menunjukkan bahwa struktur tanah asli dikategorikan memiliki nilai aktivitas montmorillonite. Pada pengujian benda dengan variasi kombinasi maksimal (20%) bahan struktur tanah dan renolith, nilai proctor tanah asli 6,72 gr/cm3 dan setelah dikombinasikan dengan 20% renolith meningkat 10,56 gr/cm3.